Volcano-tectonic evolution of a linear volcanic ridge (Pico-Faial Ridge, Azores Triple Junction) assessed by paleomagnetic studies - Silva, Pedro (2018)
The morphology of volcanic oceanic islands results from the interplay between constructive and destructive processes, and tectonics. In this study, the analysis of the paleomagnetic directions obtained on well-dated volcanic rocks is used as a tool to assess tilting related to tectonics and large-scale volcano instability along the Pico-Faial linear volcanic ridge (Azores Triple Junction, Central-North Atlantic). For this purpose, 530 specimens from 46 lava flows and one dyke from Pico and Faial islands were submitted to thermal and alternating magnetic fields demagnetizations. Detailed rock magnetic analyses, including thermomagnetic analyses and classical high magnetic field experiments revealed titanomagnetites with different Ti-content as the primary magnetic carrier, capable of recording stable remanent magnetizations. In both islands, the paleomagnetic analysis yields a Characteristic Remanent Magnetization, which presents island mean direction with normal and reversed polarities in agreement with the islands location and the age of the studied lava flows, indicating a primary thermo-remanent magnetization. Field observations and paleomagnetic data show that lava flows were emplaced on pre-existing slopes and were later affected by significant tilting. In Faial Island, magmatic inflation and normal faults making up an island-scale graben, can be responsible for the tilting. In Pico Island, inflation related to magma intrusion during flow emplacement can be at the origin of the inferred tilting, whereas gradual downward movement of the SE flank by slumping processes appears mostly translational.